Old Age Allowance and Gender Inequality in Decision Making among Dalit in Pokhara - Ranabhat, Mala; Dhungana, Ananta Raj (Journal of Development and Social Engineering, 2022)
The main aim of this paper is to explore gender inequality in decision making role among Dalit community getting Old Age Allowance (OAA) in Pokhara. For this purpose, out of 553 Dalit respondents who were getting OAA, 131 respondents have been proportionately distributed in randomly selected four wards (13, 16, 26 and 29) of Pokhara. Information was collected from these respondents using structured questionnaire. A multistage sampling technique was applied during the sample collection. Chi-squared test was applied to find the association of different decision making role of the respondents with gender. The indicators of the decision making role of the respondents taken in this study are ‘The voice is heard more and given more importance’, ‘Advice is sought on important affairs’ and ‘Actively involved in the decision making’. The information of these indicators of decision making role of the respondents was collected before and after getting OAA among friends, in family and in society. It is found that the proportion of male is higher than the female in all the indicators of decision making role of the respondents before and after getting OAA. However, the percentage of the male and female was increased after getting OAA. Further, the decision making indicators like actively involved in the decision making in Society’ before and after getting OAA, actively involved in the decision making among friends after getting OAA, and advice is sought on important affairs in society after getting OAA have significant association with gender.